Oral Human Papillomavirus Infection in Men Who Have Sex with Men: A Systematic Review and Meta-Analysis. - Eleanor M King; Soonita Oomeer; Richard Gilson; Andrew Copas; Simon Beddows; Kate Soldan; Mark Jit; W John Edmunds; Pam Sonnenberg (PLoS ONE)
Background The epidemiology of oral human papillomavirus (HPV) infection in men who have sex with men (MSM) differs from anogenital HPV infection. The impact of HPV vaccination has, to date, largely focussed on anogenital outcomes. Vaccination of MSM in the UK has been recommended and, if implemented, baseline estimates of oral HPV prevalence will be useful. Methods We searched Medline, Embase and psycINFO databases for studies reporting prevalence, incidence, and clearance of oral HPV infection in MSM. We performed a random-effects meta-analysis and meta-regression on prevalence estimates and summarised within-study risk factors for oral HPV DNA detection and incidence/clearance rates. We also performed a meta-analysis of the effect of MSM on oral HPV prevalence compared to heterosexual men. Results 26 publications were identified. The pooled prevalence of oral HPV16 from twelve estimates was 3.0% (95%CI 0.5-5.5) in HIV-negative and 4.7% (95%CI 2.1-7.3) in HIV-positive MSM. Median age of study participants explained 38% of heterogeneity (p<0.01) in HPV prevalence estimates (pooled = 17% and 29% in HIV-negative and HIV-positive, respectively; 22 estimates). Nine studies compared MSM to heterosexual men and found no difference in oral HPV prevalence (pooled OR 1.07 (95%CI 0.65-1.74)). The clearance rate was higher than incidence within studies. Type-specific concordance between oral and anogenital sites was rare. Conclusion There was substantial heterogeneity between estimates of oral HPV prevalence in MSM populations that was partly explained by HIV status and median age.